2020
DOI: 10.1002/sctm.19-0319
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vascularization in regenerative medicine

Abstract: Therapeutic angiogenesis, that is, the generation of new vessels by delivery of specific factors, is required both for rapid vascularization of tissue‐engineered constructs and to treat ischemic conditions. Vascular endothelial growth factor (VEGF) is the master regulator of angiogenesis. However, uncontrolled expression can lead to aberrant vascular growth and vascular tumors (angiomas). Major challenges to fully exploit VEGF potency for therapy include the need to precisely control in vivo distribution of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 95 publications
0
55
0
Order By: Relevance
“…As was the case with HGF, VEGF was observed to increase the least significantly after 7 day cryotherapy. This growth factor improves skeletal muscle repair through modulation of angiogenesis, however, recent studies concerning therapeutic vascularization have demonstrated that the mechanism is regulated by PDGF BB [46]. Therefore, we conclude that a decrease in the synthesis and secretion of HGF, IGF-1, PDGF BB , and VEGF can delay muscle regeneration in athletes.…”
Section: Discussionmentioning
confidence: 66%
“…As was the case with HGF, VEGF was observed to increase the least significantly after 7 day cryotherapy. This growth factor improves skeletal muscle repair through modulation of angiogenesis, however, recent studies concerning therapeutic vascularization have demonstrated that the mechanism is regulated by PDGF BB [46]. Therefore, we conclude that a decrease in the synthesis and secretion of HGF, IGF-1, PDGF BB , and VEGF can delay muscle regeneration in athletes.…”
Section: Discussionmentioning
confidence: 66%
“…This likely reflects the basic principle that is easier to bring down a house than to build one new. Understanding basic pro-angiogenesis principles will be crucial to achieve a clinical benefit for patients suffering from cardiovascular ischemic disease such as coronary artery disease or peripheral artery disease [45][46][47][48]. It will also be relevant for tissue regeneration, since poor blood vessel growth is one commonality in all types of chronic wounds leading to poor wound bed perfusion and granulation tissue formation [49].…”
Section: Angiogenesis Translational Researchmentioning
confidence: 99%
“…Upon reaching the first confluence, rBMSC were FACS purified in order to remove non-transduced cells and to yield pure CD4-positive populations ( Figure 1C), which were replated for in vitro cell expansion. Removal of non-transduced cells was done to ensure a homogeneous distribution of the signal throughout the constructs, because VEGF binds tightly to extracellular matrix and therefore remains highly localized in the microenvironment around each producing cell in vivo and does not diffuse through tissue (Ozawa et al, 2004;Gianni-Barrera et al, 2020). Production of VEGF protein by VEGF-expressing rBMSC was confirmed by ELISA (609.5 ± 284.6 ng/10 6 cells/day of rabbit VEGF), whereas naïve and CD4-rBMSC secreted background amounts (23.5 ± 22.9 and 24.2 ± 25.9 ng/10 6 cells/day, respectively).…”
Section: Generation Of Facs-sortable Vegf-expressing Rbmscmentioning
confidence: 99%
“…Vascular Endothelial Growth Factor (VEGF) is the master regulator of blood vessel growth and the key molecular target of strategies to promote vascular network expansion in regenerative medicine (Gianni-Barrera et al, 2020). Here, we test the hypothesis that increased angiogenic stimulation from within the core of bone constructs by VEGF can significantly accelerate early vascular in-growth, improve graft perfusion and therefore ensure cell viability deeper in the construct.…”
Section: Introductionmentioning
confidence: 99%